An unusual presentation of anterior urethral valve in a child with diabetes mellitus - Nerli, Rajendra B.; Sharma, Manas; Ghagane, Shridhar C; Dixit, Neeraj S; Hiremath, Murigendra B (Indian Journal of Case Reports, 2018)
Anterior urethral valve (AUV) is identified to be a common source of congenital obstructive lesion of the anterior urethra. Up to 80% of children with AUVs develop bladder dysfunction, bladder instability, hyperreflexia, diminished compliance and capacity. We report a case of an unusual presentation of a child with AUV and diabetes mellitus.